Parental satisfaction and its associated factors towards neonatal intensive care unit service: a cross-sectional study - Yewlsew Fentie Alle; Bantigegn Akenaw; Shimelis Seid; Samuel Debas Bayable (BMC Health Services Research, 2022)
Abstract Background Parental satisfaction is a well-established outcome indicator and tool for assessing a healthcare system’s quality, as well as input for developing strategies for providing acceptable patient care. This study aimed to assess parental satisfaction with neonatal intensive care unit service and its associated factors. Method A cross-sectional study design was conducted on parents whose neonates were admitted to the neonatal intensive care unit at Debre Tabor Comprehensive Specialized Hospital, in North Central Ethiopia. Data were collected by adopting an EMPATHIC-N instrument during the day of neonatal discharge, after translating the English version of the instrument to the local language (Amharic). Both Bivariable and multivariable logistic analyses were done to identify factors associated with parental satisfaction with neonatal intensive care unit service. P < 0.05 with 95% CI was considered statistically significant. Results The data analysis was done on 385 parents with a response rate of 95.06%. The overall average satisfaction of parents with neonatal intensive care unit service was 47.8% [95% CI= (43.1–52.5)]. The average parental satisfaction of neonatal intensive care unit service in the information dimension was 50.40%; in the care and treatment dimension was 36.9%, in the parental participation dimension was 50.1%, in the organization dimension was 59.0% and the professional attitude dimension was 48.6%. Gender of parents, residency, parental hospital stay, birth weight, and gestational age were factors associated with parental satisfaction. Conclusion There was a low level of parental satisfaction with neonatal intensive care unit service. Among the dimensions of EMPATHIC-N, the lowest parental satisfaction score was in the care and treatment while the highest parental satisfaction score was in the organization dimension.